(untitled) (Scientific journal of the Fergana State University, 2024)
As the world economy develops and inter-country integration relations become stronger, labor migration is becoming more and more intensive. The continuous deepening of differences between developed countries and low-developing countries has a strong influence on the acceleration of these processes. At the current stage of human society development, labor migration is a special type of migration carried out in order to find a decent job and high income, and has become one of the main means of solving the acute problems of employment and wages in underdeveloped countries with a difficult economy. During the years of independence in Uzbekistan, fundamental reforms were implemented in all areas of the economy. The attitude towards forms of ownership has changed. The emergence of an economic system based on market relations had a significant impact on the employment of the population. As a result, external labor migration occurred while increasing the employment of the country’s population. Along with a number of positive aspects, foreign labor migration has a significant impact on the development of demographic processes. For this purpose, this article tried to study the impact of foreign labor migration on demographic processes. Many disciplines, including economists, economic geographers, demographers and representatives of other disciplines study the population, its dynamics and forecast. Among them, economic geographers take an important place and study the number, dynamics, composition and territorial differences of the population, as well as ways to solve problems. In the article, migration issues, especially the impact of foreign labor migration on demographic processes, were studied using the sociological survey method.